Augmented renal clearance in critically ill patients with cancer (ARCCAN Study): A prospective observational study evaluating prevalence and risk factors - Lama H. Nazer; Aseel K. AbuSara; Yasmeen Kamal (Wiley, 2021)
Abstract Augmented renal clearance (ARC) is a phenomenon that has been associated with enhanced excretion of renally eliminated drugs, such as antimicrobials, which may result in subtherapeutic levels and potentially therapeutic failure. There has been limited data on ARC in critically ill patients with cancer. This study aimed to evaluate the prevalence of ARC and to identify risk factors associated with ARC in this patient population. This was a prospective study at an oncologic intensive care unit (ICU) which included adult patients with normal renal function, defined as serum creatinine ≤1 mg/dl and urine output >0.5 ml/kg/hr. The 24‐hour creatinine clearance (ClCr) study was used to determine ClCr, starting on day 1 of ICU admission, for 5 days or until ICU transfer or death. ARC was defined as ClCr >130 ml/min/1.73 m2. Univariate and multivariate logistic regression analyses were performed to identify risk factors for ARC. Over the study period, 363 patients were enrolled who completed an average of 2.8 ± 1.5(SD) days in the study and contributed 977 ClCr measurements. The mean age was 52 ± 16(SD) years old, the majority had solid tumors (n = 264, 73%), mean APACHE II was 21 ± 8(SD), and the major admission diagnosis was respiratory failure (n = 165, 45%). ARC was reported in 116 (32%) patients on at least one of the study days. Over the study period, the incidence of ARC ranged between 15.6% and 24.3%. Age was the only risk factor significantly associated with ARC (OR 1.028, 95% CI 1.005-1.051).